الدور التنموي للمستدام للسندات الخضراء بين الايجابيات والسلبيات - بوصبيع صالح, رحيمة; حملاوي, سكينة (جامعة الوادي - University of Eloued, 2023)
This research paper, aims to study the role of green finance with green bonds in financing sustainable development, by addressing : their types, principles, and areas that finance them and clarifying their financing role for low-carbon sectors. This study concluded that: The general orientation of green bond financing, its mechanisms of action, and the sectors that finance it makes it an important tool to support sustainability, despite its weak current impact as it is newly established, in addition to the absence of a completely green sector or activity.
The sustainable development role of green bonds between positives and negatives
مقال
Keywords: تمويل أخضر، سندات خضراء، تنمية مستدامة، اصدار السندات الخضراء، المشاريع الخضراء: Green Finance; Green Bonds; Sustainable Development; Issuance of green bonds; Green projects.